Aquatic Ecosystem: Biodiversity, Ecology and Conservation - Rawat, Mamta; Dookia, Sumit; Sivaperuman, Chandrakasan (Springer India : Imprint: Springer, 2015)
This book brings together the latest information on the rapid advances and developments in the field of aquatic ecology. India is very rich in terms of biological diversity due to its wide range of habitats and climatic conditions. It is home to as much as 7 per cent of the world's animal species, although it only accounts for about 2 per cent of the total landmass. The present work on biodiversity, ecology and conservation of aquatic resources represents original research in the field of aquatic biodiversity, wetland ecology and its applications with reference to the country's aquatic resources. There are 19 chapters, each contributed by an expert in his/her particular field and offering novel approaches to various topics in the area of aquatic ecosystems.